2021
DOI: 10.1186/s13023-021-01994-z
|View full text |Cite
|
Sign up to set email alerts
|

Hospital mortality in patients with rare diseases during pandemics: lessons learnt from the COVID-19 and SARS pandemics

Abstract: Background The threat and experience of pandemics occur differently for different groups. The rare disease population is at particular risk of being further marginalised during pandemics. In this study, our objective was to assess the hospital mortality patterns in the rare disease and the general populations during the coronavirus disease of 2019 (COVID-19) and severe acute respiratory syndrome (SARS) pandemics in Hong Kong. Methods All admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Our results are in line with early reports by the Hong Kong study done by Chung et al, in which increased COVID-19-related hospital mortality was observed (mOR = 3.4, 95% CI 1.24–9.41) in rare disease patients compared with the general population, after adjusting for admission age [ 9 ]. There are two differences in the settings in our study: (1) our cohort includes individuals with positive Sars-CoV-2 tests, while the cohort of the Hong Kong study only considered hospitalised patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with early reports by the Hong Kong study done by Chung et al, in which increased COVID-19-related hospital mortality was observed (mOR = 3.4, 95% CI 1.24–9.41) in rare disease patients compared with the general population, after adjusting for admission age [ 9 ]. There are two differences in the settings in our study: (1) our cohort includes individuals with positive Sars-CoV-2 tests, while the cohort of the Hong Kong study only considered hospitalised patients.…”
Section: Discussionsupporting
confidence: 93%
“…To date, direct analysis on the risk of COVID-19 mortality among people with rare diseases is still limited. In a Hong Kong study by Chung et al increased COVID-19 related mortality was observed in hospitalised patients with rare diseases compared to the general population, but other COVID-19 related commodities were not accounted for [ 9 ]. To address the above challenge, we utilised data in the Genomics England 100k Genomes project, which has a specific focus on recruiting rare-disease patients with clinical diagnosis available [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 A more recent study showed that hospital mortality due to COVID-19 was enormously increased in these patients. 6 The same study also reported a higher in-hospital mortality due to non-COVID-19 reasons when compared with pre-pandemic numbers. Although a worse prognosis of COVID-19 is predictable in genetically inherited rare diseases such as GD, there is not yet sufficient information in the literature.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, anxiety and depression were reported at a higher prevalence among patients with a rare disease than in the general population 5 . A more recent study showed that hospital mortality due to COVID‐19 was enormously increased in these patients 6 . The same study also reported a higher in‐hospital mortality due to non‐COVID‐19 reasons when compared with pre‐pandemic numbers.…”
Section: Introductionmentioning
confidence: 94%
“…However, patients with PKU are less subjected to such influences than most patients with IMD. Tummolo et al [ 22 ] reported a moderate influence of the COVID-19 pandemic on a relatively numerous cohort of IMD patients, which included children and young adults, but Chung et al established that patients with rare diseases had a 3.4 times higher OR of hospital death from COVID-19-related causes than the general population [ 23 ].…”
Section: Discussionmentioning
confidence: 99%